ANALISIS PELAYANAN PUBLIK TERHADAP TINGKAT KEPUASAN MASYARAKAT DI DESA LAGADING KECAMATAN PITU RIASE KABUPATEN SIDENRENG RAPPANG - Fatmawati; Sellang, Kamaruddin; Adnan, Andi Astina (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to determine the Public Service Analysis of the Level of Community Satisfaction in Lagading Village, Pitu Riase District, Sidenreng Rappang Regency. The population in this study was 47 people who received services in November and December in Lagading Village, Pitu Riase District, Sidenreng Rappang Regency. The sampling technique uses a saturated sample where the entire population is sampled. This type of research is quantitative descriptive. The data collection techniques used in this research were observation, literature study and questionnaires. The data analysis technique used is validity and reliability testing, using the IBM SPSS statistics 26.0 application. The results of this research showed that the Public Service Analysis from the results of the questionnaire obtained a recapitulation of public service variables of 61% in the "good" category, and a recapitulation of public satisfaction level variables of 67% in the "Good" category. Apart from that, the influence between Public Service Analysis and the level of community satisfaction in Lagading Village is categorized as "influential/significant". From the ANOVA test, the F count obtained was 101.683 with a significance level of 0.003. This shows that the influence of the independent variable has a significant effect, and the probability is far above 0.05, partially. The calculated t value (1,084) ≥ t table (1,673) means that the analysis of public services is influential/significant on the level of community satisfaction in Lagading Village, Pitu Riase District, Sidenreng Rappang Regency.